Genotoxicity, anti-melanoma and antioxidant activities of hymenaea courbaril L. Seed extract - Spera, Kamille D. [UNESP]; Figueiredo, Patrícia A. [UNESP]; Santos, Pamela C. E. [UNESP]; Barbosa, Fernando C. [UNESP]; Alves, Caio P. [UNESP]; Dokkedal, Anne Lígia [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Silva, Luciana P.; Figueiredo, Carlos Rogério; Ferreira, Paulo Cesar [UNESP]; Da Silva, Regildo M. G. [UNESP] (FapUNIFESP (SciELO), 2019)
Hymenaea courbaril has been used to treat different diseases, although its properties are yet to be scientifically validated. The objective of this study was to determine the cytotoxicity, genotoxicity, antigenotoxicity and antioxidant potentials of hydroethanolic extract from H. courbaril seeds. Therefore, for the cytotoxicity test an anti-melanoma assay was performed in B16F10 strain cells. The genotoxicity and antigenotoxicity was evaluated in bone marrow cells (Permit number: 002/2010) of mice, the antioxidant activity was determined by the DPPH test and the total flavonoid content was also determined. The hydroethanolic extract showed antigenotoxic effect and antioxidant activity. It was verified that total flavonoid content was 442.25±18.03 mg RE/g dry extract. HPLC-PAD chromatogram revealed presence of flavones as majority compound in evaluated extract. The results allowed us to also infer that the hydroethanolic extract from seeds shows cytotoxic activity against B16F10 melanoma cells line and it has dose-and-time-dependency.
Keywords: B16F10 melanoma cells; Chromosomal aberration; DPPH radical scavenging; HPLC-DAD; Micronucleus test